Epithelial to mesenchymal transition pathway in pituitary endocrine tumours - Reis, Fábio Domingues Carril (2023)
Abstract Adenohypophyseal tumors, which were recently renamed pituitary neuroendocrine tumors (PitNET), are mostly benign tumours arising from adenohypophysis cells. The interation between elements within the microenvironment and tumor cells PitNETs, with a special emphasis on cytokines, has a substantial impact on various aspects of cancer-related processes. This includes the aggressiveness of tumors and how they respond to treatments. Among these cytokines, CCL2 has emerged as a central figure in PitNETs, although its precise biological role remains somewhat elusive. One possible explanation for its function is its influence on a process known as the epithelial-to-mesenchymal transition (EMT). EMT is a biological phenomenon where epithelial cells undergo significant transformations, including the loss of their characteristic cell polarity and the acquisition of heightened migratory capabilities. This transformation leads to increased invasiveness, aggressiveness, and resistance to treatment. A hallmark of EMT is the reduction in the expression of epithelial markers like E-cadherin, accompanied by the overexpression of mesenchymal markers like ZEB-1. In the context of pituitary neuroendocrine tumors (PitNETs), EMT remains a relatively unexplored area of study. We hypothesize that CCL2 contributes to shaping the characteristics and prognostic outcomes of PitNETs. So, with this work, we aimed to explore how CCL2 influences the epithelial-to-mesenchymal transition (EMT) pathway, with a strong focus on understanding its impact on the levels of E-cadherin and ZEB-1 expression. Additionally, we sought to determine the relationship between these molecular changes and the clinical features and outcomes observed in PitNET patients. To carry out our objectives we analyze the expression of CDH1 (which encodes E-cadherin, an epithelial marker) and ZEB1 (mesenchymal marker) and CCL2 by RT- qPCR on 86 PitNETs from patients who underwent surgery at our center between 2014-2020: 62 nonfunctioning-PitNETs (NF-PitNETs), 18 somatotropinomas and 6 corticotropinomas. CHD1, ZEB-1 and CCL2 expression was then correlated with clinico-pathological, outcome data, and CCL2 expression was also correlated with E-cadherin expression. In vitro experiments were also performed, these included proliferation assays, western blots, RT-PCR, immunofluorescence assays and morphology measurements. In our cohort, 47.7% were males, age at diagnosis was 56±15yr (mean±SD), and mean follow-up was 6±4yr. CCL2 mRNA expression did not differ among PitNET types, in the whole cohort, higher CCL2 mRNA expression was seen in males, patients who had hypopituitarism at diagnosis, and in patients who more often required multimodal therapy, needed more treatments and had active disease at last-follow-up. . CCL2 mRNA expression levels negatively correlated with CDH1 expression levels. Regarding the in vitro data, CCL2 appeared to have an anti-proliferative effect on GH3 cells. In addition, we did not observe a significant gain in the migration ability of GH3 cells in the presence of CCL2, in the transwell migration assay. Also, CCL2 did not induce significant morphological changes on GH3 cells. Nevertheless, our preliminary immunofluorescence experiments allowed us to detect the formation of filopodia in cells conditioned with rCCL2. Also, ZEB-1 mRNA expression levels were increased in cells conditioned with 5ng/ml rCCL2, consistent with a migratory phenotype, seemingly impacting EMT. Considering our results collectively, incorporating the assessment of CCL2 expression in human Pituitary Neuroendocrine Tumors (PitNETs) as a routine clinical practice, such as including it in pathology reports, may offer valuable prognostic insights, particularly in predicting the presence of more aggressive and challenging-to-treat PitNETs, working as a biomarker. However, the absence of a clear connection between CCL2 and the behavior of pituitary tumors in our in vitro experiments suggests that a prominent independent role in determining the aggressiveness of pituitary tumor cells by CCL2 alone, cannot yet be confirmed. Consequently, it does not currently justify the development or implementation of immunotherapy specifically designed to block or inhibit CCL2.